Tribal Knowledge in Early Childhood Education: A Ngāti Te Ata Waiohua Case Study - Cornhill, Desma (Auckland University of Technology, 2014)
The research has been designed to examine the overarching query: How tribal knowing is implicated in teaching and learning in early childhood education. Accordingly, this study is an investigation into the links between tribal epistemology and early childhood education and care: Specifically Ngāti Te Ata Waiohua tribal knowledges. Tribal curricula and pedagogical approaches to teaching and learning with young children are examined through kaiako (teachers) narrative. In early childhood education, there is contention regarding what comprises knowledge, skills and attitudes in the teaching and learning of young children. A machination of factors including global economics and industry has an impact on early childhood education curriculum. Ngāti Te Ata Waiohua tribal knowledges appear subjugated; thereby creating tensions for local tribal aspirations. This study argues that Ngāti Te Ata Waiohua tribal epistemology is powerful in providing a site of freedom, innovation and transformation through the care and education of young children. This examination calls into focus the intersection between Ngāti Te Ata Waiohuatanga (Ngāti Te Ata Waiohua tribal epistemology), Te Kāhui Iti Nei o Te Kōpū Puna Reo (Ngāti Te Ata Waiohua tribal early childhood education and care service) and teacher pedagogical approaches to teaching and learning of young children. As such it stimulates further thinking around the symbiotic nature of tribal development and early childhood education.
Keywords: Tribal knowledge; Early childhood education